Boosting sticking-dependent transmission studies to a single TPMC simulation. (April 2023) - Kiesel, Stefan; Trützschler, Andreas; Bergner, Klaus
Abstract: Particle transmission probabilities through vacuum ducts in molecular flow regime are dependent on the sticking probability of particles to the duct walls. Test particle Monte-Carlo (TPMC) simulations of transmission probabilities for various sticking coefficients are connected with considerable computational effort, since a separate simulation is necessary for each value. Here, we introduce a theoretical approach based on counting particle-wall interactions during transmission, which reduces the amount of simulations to a single run. Application of this calculation scheme to simulations of an elbow geometry, and statistical analysis of the simulation results are shown. Highlights: Transmission probabilities for all sticking factors s in a single TPMC simulation. Record histograms of transmitted particles with bounces N before absorption. Multiply s = 0-histograms with (1-s)^N to calculate histogram for s > 0. Histograms are divided by desorptions and summed for total transmission probability.